Consumer Panic Buying in the COVID-19 Pandemic Era - Dicky Wisnu Riyanto; Viajeng Purnama Putri (Manajemen Bisnis, 2021)
This study is to examine the effect of the relationship between scarcity promotion, consumer competition, on impulse purchases. Data were collected using a questionnaire, a sample of 100 respondents was taken based on purposive sampling. Data analysis using Partial Least Square (PLS), this path analysis technique will be used in testing the magnitude of the contribution shown by the path coefficients on each path diagram of the causal relationship between SP, KK, and IP variables. The findings reveal that scarcity promotion, consumer competition, affects impulse purchases positively and significantly. Consumer competition mediates the relationship between scarcity promotion and impulse purchase. The better the scarcity promotion, the higher the consumer's impulse purchase.